Towards devising a fundamental theory of Islamic advertising - Abdullah, Kalthom; Haque, A. K. M. Ahasanul; Ahmed, Faruk; Shafiq, Ali (2016)
Advertising plays a significant role on socio-economic fronts. It not only lubricates the economic traffic, but also raises the standard of living by offering newer and better products. But at the same time advertising is not without criticism. Critics say advertising is the cause of many socio-economic evils. Polluting the moral and cultural values, encouraging overspending and materialism, and general dissatisfaction with products while offering little added value are some of its common criticisms. With the rise in unethical practices in contemporary advertising without any hope of improvement, the practitioners and consumers are searching for ‘sustainable’ alternatives. Islamic advertising offers a solution – theoretically so far. There are general guidelines in the Holy Quran and the Sunnah regarding how an Islamic mode of advertising should be. The Islamic scholars have done a commendable job of extracting specific guidelines from them, yet a comprehensive theory for Islamic advertising is to be formed. Previous research has mainly focused on conventional advertising with only a glimpse on theory of advertising. This research aims is to seek a prevalent gap and strive to develop a comprehensive theory of Islamic advertising.